Acceptability Crispy Cheese Tuile with Main Ingredients Canna Starch Flour and Mung Bean Flour - Benazhir Angelia Maghribi; Sri Subekti; Cica Yulia (Media Pendidikan Gizi dan Kuliner, 2022)
Crispy cheese tuileis one of the cookies that comes from France. The main ingredient for making these cookies is wheat flour. Canna starch flour comes from canna tubers which are easy to cultivate intensively but their utilization is not maximized. Canna starch flour has the potential as a source of carbohydrates and high quality starch. Mung bean flour comes from mung bean seeds which is a food plant that is easy to cultivate and has high protein. Canna starch flour and mung bean flour can be developed into pastry products to replace wheat flour whose ingredients must be imported. The purpose of this study was to obtain a recipe for crispy cheese tuile, to know the sensory analysis of crispy cheese tuile with the main ingredients of canna starch and mung bean flour. and knowing consumer acceptance of crispy cheese tuile products with the main ingredients of canna starch and mung bean flour. This study used RAL (Completely Randomized Design). The instrument used is a questionnaire in the form of a checklist. The panelists in the study were 30 untrained panelistsof the three formulas for crispy cheese tuile with code 169 (80% canna starch: 20% mung bean flour), code 507 (50% canna starch: 50% mung bean flour), and code 307 (20% canna starch: 80 % green bean flour). Based on sensory analysis, the most preferred recipe formula is code 169. The highest level of preference for the color, taste, aroma, texture, and overall category is for products with code 169. The results of the acceptability analysis, codes 169 and 307 are in the very acceptable category and code 507 accepted.